Relationships among Factual and Perceived Knowledge of Harms of Waterpipe Tobacco, Perceived Risk, and Desire to Quit among College Users - Lipkus, Isaac M. (J Health Psychol, 2013)
Waterpipe tobacco smoking (WTS) is increasing in the U.S among college students. Through a web-based survey, we explored associations among factual and perceived knowledge, perceived risks and worry about harm and addiction, and desire to quit among 316 college WTS users. Overall, factual knowledge of the harm of WTS was poor; factual and perceived knowledge were weakly correlated; both forms of knowledge were related inconsistently to perceived risks and worry, and neither form of knowledge was associated with the desire to quit. Findings provide preliminary insights as to why knowledge gaps may not predict cessation among waterpipe users.